PENGGUNAAN JENIS BAHASA SERTA INTERAKSI KOMUNITAS PEDAGANG ASONGAN DENGAN WISATAWAN MANCANEGARA DI KAWASAN WISATA PANTAI KUTA, KECAMATAN KUTA, KABUPATEN BADUNG - Wiranata, Anak agung Tirta Putra; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2016)
This field research aims to determine the type of language used by merchant as well their interaction while offering their wares to international tourist. This field research is interesting because, people do not know what kind of language that is often used by merchant when interacting with international tourist while selling their wares. Even with the limitation of language, this phenomenon does not prevent merchant to communicate with international tourist. The data is analyzed qualitatively. It is collected by structured observation, semi-structured interviews, and documentation study. Whereas, the informants and samples are determined by using Purposive Sampling technique, which was to determine the sample with a certain consideration, which considered to be able to provide the data to the maximum in accordance with the criteria of the research objectives. The results of the field research states that the type of language used by the merchant in the tourist area of Kuta Beach was pidgin language, because it did not have a native speaker criterion. Pidgin language is a language that does not have native speakers as well as just a means of communication between people - those who do not understand each other. It was seen the merchant on Kuta Beach came from various regions in Indonesia, such as Sumatra, Java, and Bali. It was considered they had been taught since birth with each regional language (mother tongue), not the language that now they use to interact with international tourist. Meanwhile, when the process of interaction between merchant who are offering their wares to international tourist, it was aided with the help of body gestures. This behavior or symbol was being used in the process of interaction between merchant and international tourist, so that them would understand the purpose of the merchant.
Keywords: Type of Language, Pidgin, Interaction, Merchant, International Tourist, Kuta Beach.